Evaluation of a SARS‐CoV‐2 antigen‐detecting rapid diagnostic test as a self‐test: Diagnostic performance and usability. Issue 12 (26th August 2021) - Cassuto, Nino Guy; Gravier, Anne; Colin, Mathilda; Theillay, Aurelie; Pires‐Roteira, Daniela; Pallay, Sandra; Serreau, Raphael; Hocqueloux, Laurent; Prazuck, Thierry
Abstract: To control the spread of the coronavirus disease 2019 (COVID‐19) epidemics, it is necessary to have easy‐to‐use, reliable diagnostic tests available. The nasopharyngeal sampling method being often uncomfortable, nasal sampling could prove to be a viable alternative to the reference sampling method. We performed a multicentre, prospective validation study of the COVID‐VIRO® test, using a nasal swab sampling method, in a point‐of‐care setting. In addition, we performed a multicentre, prospective, and usability study to validate the use of the rapid antigen nasal diagnostic test by laypersons. In March 2021, 239 asymptomatic and symptomatic patients were included in the validation study. Compared with reverse‐transcription polymerase chain reaction on nasopharyngeal samples, the sensitivity and specificity of the COVID‐VIRO® Antigen test combined with a nasal sampling method were evaluated as 96.88% and 100%, respectively. A total of 101 individuals were included in the usability study. Among these, 99% of the participants rated the instructions material as good, 98% of the subjects executed the test procedure well, and 98% of the participants were able to correctly interpret the test results. This study validates the relevance of COVID‐VIRO® as a diagnostic tool from nasal specimens as well as its usability in the general population. COVID‐VIRO® diagnostic performances and ease of use make it suitable for widespread utilization.